Application of D-STATCOM for load compensation with non-stiff sources - 1Shubhangi Dhole; Vinayak Patil; Pushkraj Kharatmal (International Journal of Innovations in Engineering Research and Technology, 2021)
Now a day’s power quality is serious problem inpower network. To overcome this problem an innovative deviceD-STATCOM is used. D-STATCOM (distribution static compensator) is facts device used to solve all power quality problems which connected in parallel with system. The main function of D-STATCOM is, it generates or absorbs the reactive power at point of common coupling (PCC), so that power quality can be maintained. Power quality problems are important issue in distribution system. In this paper new method for D-STATCOM with non-stiff sources is proposed for the load compensation it also considers linear and non linear loads.